A Test of Audit Pricing in the Small-Client Segment of the U.S. Audit Market. - Francis, Jere R.; Simon, Daniel T. (The Accounting Review, 1987)
Abstract ABSTRACT: Simunic [1980] and Palmrose [1986, Appendix A] report contradictory findings about a Big Eight auditor price premium In the "small" auditee segment of the U.S. audit market for publicly-traded companies. The study reported here finds that a Big Eight price premium exists and that the premium exists with respect to both second-tier national firms and local/regional firms. The existence of a price premium Implies Big Eight product differentiation, at least in the "small" auditee market segment. A separate test is made of initial audit engagements. Tests indicate that initial engagements are priced significantly lower than continuing engagements, which supports recent reports of price-cutting behavior. However, no inference is made about the effect of price-cutting on audit quality.